Critical Analysis of Parole Evidence in Law of Contract. - Bashir, Sobia; Khan, Abdus Samad; Nisar, Kiran (Journal of Peace, Development and Communication, 2023)
The parol evidence rule is a crucial concept in contract law that restricts the use of extrinsic evidence to alter or contradict the provisions of a written agreement. The principle is grounded on the notion that once parties have documented their contract in writing, the written contract should be regarded as the comprehensive and definitive representation of their intentions. While there are exceptions and limitations to the rule, it generally applies to integrated written agreements and is designed to promote certainty and predictability in contractual relationships. Courts have issued numerous decisions interpreting and applying the parol evidence rule, and it remains an important and often litigated aspect of contract law.